2015
DOI: 10.1089/neu.2014.3451
|View full text |Cite
|
Sign up to set email alerts
|

Long-Lasting Suppression of Acoustic Startle Response after Mild Traumatic Brain Injury

Abstract: Acoustic startle response (ASR) is a defensive reflex that is largely ignored unless greatly exaggerated. ASR is suppressed after moderate and severe traumatic brain injury (TBI), but the effect of mild TBI (mTBI) on ASR has not been investigated. Because the neural circuitry for ASR resides in the pons in all mammals, ASR may be a good measure of brainstem function after mTBI. The present study assessed ASR in Sprague-Dawley rats after mTBI using lateral fluid percussion and compared these effects to those on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
26
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 42 publications
5
26
0
Order By: Relevance
“…1–2, based on n=2 sham and n=3 FPI rats). However, contralateral hippocampal neuronal degeneration has been reported at later time points after FPI and cortical impact (Colicos et al, 1996; Neese et al, 2007; Pang et al, 2014), possibly due to secondary neuronal injury. Since neuronal injury and death can activate the innate immune responses, we used Western blot analysis to quantify hippocampal TLR4 protein levels at various time points after FPI.…”
Section: Resultsmentioning
confidence: 99%
“…1–2, based on n=2 sham and n=3 FPI rats). However, contralateral hippocampal neuronal degeneration has been reported at later time points after FPI and cortical impact (Colicos et al, 1996; Neese et al, 2007; Pang et al, 2014), possibly due to secondary neuronal injury. Since neuronal injury and death can activate the innate immune responses, we used Western blot analysis to quantify hippocampal TLR4 protein levels at various time points after FPI.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies have shown that sensorimotor coordination measured as the ASR is altered in a rodent models of TBI but only one has utilized a mouse model 8, 11, 12 . To take advantage of the powerful tools provided by genetic engineering, many investigators in the field of neurotrauma have shifted from rat to mouse models.…”
Section: Discussionmentioning
confidence: 99%
“…All rats were assessed for acoustic startle reflex (ASR) because we previously found suppression of ASR to be a consistent outcome of mTBI following lateral fluid percussion injury. [32][33][34] Assessment of ASR was performed as previously described. 32 ASR was assessed in individual, sound-attenuated chambers, each equipped with an exhaust fan, one speaker to maintain background noise (68dB) and another speaker for delivery of the acoustic stimuli (86, 96, and 102dB; 100 ms).…”
Section: Acoustic Startle Reflexmentioning
confidence: 99%
“…[32][33][34] Assessment of ASR was performed as previously described. 32 ASR was assessed in individual, sound-attenuated chambers, each equipped with an exhaust fan, one speaker to maintain background noise (68dB) and another speaker for delivery of the acoustic stimuli (86, 96, and 102dB; 100 ms). A single session consisted of 24 trials (8 repetitions of 3 intensities), in which the acoustic stimulus was presented immediately after a 250ms baseline period.…”
Section: Acoustic Startle Reflexmentioning
confidence: 99%
See 1 more Smart Citation